2023
DOI: 10.3389/fonc.2022.1086821
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatments for breast cancer brain metastasis

Abstract: Breast cancer (BC) is the most common cancer in females and BC brain metastasis (BCBM) is considered as the second most frequent brain metastasis. Although the advanced treatment has significantly prolonged the survival in BC patients, the prognosis of BCBM is still poor. The management of BCBM remains challenging. Systemic treatments are important to maintain control of central nervous system disease and improve patients’ survival. BCBM medical treatment is a rapidly advancing area of research. With the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…The median survival of patients with BC with BMs who did not receive any treatment was approximately 10 months [ 33 ]. Previous studies have shown that patients with TNBC and HER2-positive BC have shorter median survival times, whereas those with HR-positive BC have longer median survival times.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival of patients with BC with BMs who did not receive any treatment was approximately 10 months [ 33 ]. Previous studies have shown that patients with TNBC and HER2-positive BC have shorter median survival times, whereas those with HR-positive BC have longer median survival times.…”
Section: Discussionmentioning
confidence: 99%